Thermal treatment of a potassium-rich metamorphic rock in formation of soluble K forms - Santos, Wedisson Oliveira; Mattiello, Edson Marcio; Pacheco, Anderson Almeida; Vergutz, Leonardus; Souza-Filho, Luiz Francisco da Silva; Abdala, Dalton Belchior (International Journal of Mineral Processing, 2017)
Countries like Brazil, China and India are highly dependent on external reserves of soluble potassium (K) minerals for the production of K fertilizers. On the other hand, the natural occurrence of potassium-rich silicate minerals in these countries, has seldom been commercially exploited until recently. Technological strategies that can increase the reactivity of these minerals can turn them into a resource for K fertilizer production. This work aimed to investigate the changes in solubility of Verdete rock (VR) after calcination with a melting agent (MA- CaCl2·2H2O) under varying temperatures of calcination and ratios (w w− 1) of MA/VR. Measurements of extractable K in water (Kwater), X-ray diffraction (XRD) and X-ray Absorption Near Edge Structure (XANES) were performed to identify new mineral phases. The Kwater increased up to 184-fold when the VR was calcined in the presence of MA. Optimization of calcination of VR to temperature of 850 °C and a 1.7 ratio (w w− 1) of MA/VR yielded Kwater values of up to 95% of total K. Potassium K-edge XANES analysis revealed changes in the molecular environment of K due to the calcination of VR at increasing temperatures. The K K-edge XANES fit to sylvite was supported by the detection of this mineral by XRD analysis at calcination temperatures ranging from 700 to 900 °C. In addition, K K-edge XANES analysis indicated the gradual formation of a new potassium-silicate mineral with increasing temperature, which the XANES analysis showed to be an amorphous-K2SiO3 (Amorphous-K2SiO3). The combination of Kwater and the residue of Linear Combination Fitting analysis (LCF) performed on the XANES data suggested the formation of an undefined K mineral phase additional to sylvite and Amorphous-K2SiO3. The calcination process was effective in producing highly soluble K mineral phases from a low solubility raw material. The end-products of the calcination procedure obtained in our work represent a promising alternative material for K fertilizer production, but further evaluation of the plant availability of the K in soils is needed.
Keywords: Calcination; Calcium chloride; Glauconitic rock